2017
DOI: 10.1371/journal.pmed.1002335
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density and ageing: A collaborative pooled analysis of cross-sectional data from 22 countries worldwide

Abstract: BackgroundMammographic density (MD) is one of the strongest breast cancer risk factors. Its age-related characteristics have been studied in women in western countries, but whether these associations apply to women worldwide is not known.Methods and findingsWe examined cross-sectional differences in MD by age and menopausal status in over 11,000 breast-cancer-free women aged 35–85 years, from 40 ethnicity- and location-specific population groups across 22 countries in the International Consortium on Mammograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 41 publications
(60 reference statements)
11
113
1
3
Order By: Relevance
“…Multiple studies have shown high mammographic density to be associated with interval cancers(4446), including our own findings herein. However, it is difficult to disentangle tumor biology and mammographic density because younger women have both higher density and more aggressive tumor characteristics(47,48). We were unable to consider the independent contributions of age, race, and mammographic density due to sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown high mammographic density to be associated with interval cancers(4446), including our own findings herein. However, it is difficult to disentangle tumor biology and mammographic density because younger women have both higher density and more aggressive tumor characteristics(47,48). We were unable to consider the independent contributions of age, race, and mammographic density due to sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Figure shows the SAR analysis on the phantoms of different age group at randomly picked fixed distance and power corresponding to 5 mm and 1 mW, respectively. It is found that the change in SAR values is nonsymmetrical for different patients because there is no fixed defined pattern of variation in the breast tissue density and age of the patients, breast density may differ for two individuals of the same age group . The same is evident from the aforementioned figure, that the SAR values for different age groups vary independently, even though the distance of antenna and the microwave source power are fixed with the similar antenna placed in the vicinity of all breast models.…”
Section: Resultsmentioning
confidence: 96%
“…A range of approaches have been taken to examining this issue in terms of study design as well as the method(s) used to assess mammographic density . Some studies have reported, for example, that the characteristic associations seen between mammographic density and age (or menopausal status) are seen consistently across different ethnic groups or that mammographic density is not different in women of different ethnicities, especially when data are adjusted for BMI . The picture may also be influenced by which ethnicities are considered Asian, as the picture may be different for women from East and South Asia …”
Section: Discussionmentioning
confidence: 99%